Pemisahan Asam-asam Lemak N-Metilhidroksamik Berbasis Minyak Inti Buah Ketapang menggunakan Kromatografi Cair Kinerja Tinggi - Ana Restu Nirwana; Dedy Suhendra; Erin Ryantin Gunawan (Postgraduate, University of Mataram, 2022)
N-methyl fatty hydroxamic acids (N-MFHAs) is a derivative of a hydroxamic acid (FHA), were synthesized from ketapang seed oil (Terminalia catappa L.) with N-methyl hydroxylamine enzymatically using immobilized lipase (Lipozyme TL IM). N-MFHAs that are synthesized are still in a mixed state of triglycerides of the ketapang seed oil. This research aims to determine the optimum conditions for the separation of N-MFHAs into their single components and their percentage composition using High Performance Liquid Chromatography (HPLC). The specification of the HPLC system includes using the reverse phase column SGE C-18 ODS-2 and UV detector 213 nm. The optimum conditions for the separation of N-MFHAs in the HPLC system include using the mobile phase of methanol 100% and flow rate of 0.25 mL/minutes with an injection volume of 20 ÂµL and sample concentration of 10.000 ppm. The percentage of the N-MFHAs composition successfully separated using HPLC were linoleoyl-methyl-fatty hydroxamic acid (13.09%), oleoyl-methyl-fatty hydroxamic acid (62.46%), palmitoyl-methyl-fatty hydroxamic acid (19.51%), and stearoyl-methyl-fatty hydroxamic acid (4.93%).